2019
DOI: 10.1093/mnras/stz2616
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the production and escape of ionizing radiation from the emission-line spectra of metal-poor star-forming galaxies

Abstract: We explore the production and escape of ionizing photons in young galaxies by investigating the ultraviolet and optical emission-line properties of models of ionizationbounded and density-bounded H regions, active-galactic-nucleus (AGN) narrow-line regions and radiative shocks computed all using the same physically-consistent description of element abundances and depletion on to dust grains down to very low metallicities. We compare these models with a reference sample of metal-poor star-forming galaxies and L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(152 citation statements)
references
References 142 publications
(335 reference statements)
10
141
1
Order By: Relevance
“…These emissionline diagnostic diagrams or 'BPT' diagrams separate emission-line ratios according to the source of ionizing radiation, with the overlaid 'maximum starburst line' from Kewley et al (2001) separating photoionized gas (below the line) from harder ionizing sources such as shocks and active galactic nuclei (above the line). Since all of the emission-line ratios from JKB 18 lie below the solid line, we can confirm that the gas is dominated by photoionization, however, as demonstrated by Plat et al (2019) and Kewley et al (2013), given the low metallicity of the gas, contributions from shock excitation cannot be ruled out. Both diagnostics maps show an interesting ionization structure -while the central star-forming region (marked as 'X') shows (an expected) high [O III]/Hβ, other regions of similar excitation lie at the edges of some star-forming regions and are offset from the areas of strongest star formation (as indicated by the overlaid Hα contours), suggesting that the ionizing photons are not propagating in a uniform direction from the centre of the ionized gas and instead preferentially move towards the outer boundary of the ionized gas.…”
Section: Sources Of Ionization Across Jkb 18mentioning
confidence: 71%
“…These emissionline diagnostic diagrams or 'BPT' diagrams separate emission-line ratios according to the source of ionizing radiation, with the overlaid 'maximum starburst line' from Kewley et al (2001) separating photoionized gas (below the line) from harder ionizing sources such as shocks and active galactic nuclei (above the line). Since all of the emission-line ratios from JKB 18 lie below the solid line, we can confirm that the gas is dominated by photoionization, however, as demonstrated by Plat et al (2019) and Kewley et al (2013), given the low metallicity of the gas, contributions from shock excitation cannot be ruled out. Both diagnostics maps show an interesting ionization structure -while the central star-forming region (marked as 'X') shows (an expected) high [O III]/Hβ, other regions of similar excitation lie at the edges of some star-forming regions and are offset from the areas of strongest star formation (as indicated by the overlaid Hα contours), suggesting that the ionizing photons are not propagating in a uniform direction from the centre of the ionized gas and instead preferentially move towards the outer boundary of the ionized gas.…”
Section: Sources Of Ionization Across Jkb 18mentioning
confidence: 71%
“…The two discrepancies might arise from the fact that the models do not take into account a DIG component, which can significantly contribute to the emission of [O i] and [S ii] (Sanders et al 2017(Sanders et al , 2020. Alternatively, these discrepancies could also be attributed to the presence of shocks, which are not included in our models (see, e.g., Plat et al 2019) because of problems with atomic data for sulfur (Izotov et al 2006;Kewley & Dopita 2002;Kewley et al 2019), or others. The sulfur line ratio [S ii]/[S iii] is also sensitive to more subtle effects including stellar winds, outflows, and photoevaporation of photo-dissociation regions (PDRs) in Galactic dense gaseous environments (e.g., Westmoquette et al 2013;McLeod et al 2015).…”
Section: Diagnostics Of the Low-ionization Regionsmentioning
confidence: 99%
“…He ii, and others) and also of low-ionization lines (e.g., Schmitt 1998;Stasińska et al 2015;Plat et al 2019). The effect of a contribution from shock models with different magnetic field strengths (tuned to reproduce a typical He ii/Hβ ratio) on the O32−O13 diagram is shown in Stasińska et al (2015).…”
Section: Low Ionization Line Diagnostics: Progress and Caveatsmentioning
confidence: 99%
See 1 more Smart Citation
“…As argued by S20, even though it remains unclear whether XRBs are the dominant producers of He II ionising photons or not, binary-star models (Eldridge et al 2017) overall do a better job at producing more He II ionizing photons compared to single star models (see also Steidel et al 2016). Recent modelling of production of ionizing radiation in star-forming galaxies by Plat et al (2019) showed that the highest He II EWs are produced in low-metallicity stellar populations (both single and binary-star models) with highionization parameter values, log U ≥ −2. However, to explain the highest He II EWs observed in the literature, the stellar populations must have very young ages (log age/yr < 7).…”
Section: Other Possible Explanations For He IImentioning
confidence: 99%